A time estimation task as a possible measure of emotions: difference depending on the nature of the stimulus used - Gros, Auriane; Giroud, Maurice; Bejot, Yannick; Rouaud, Olivier; Guillemin, Sophie; Aboa Eboulé, Corine; Manera, Valeria; Daumas, Anaïs; Lemesle Martin, Martine (Frontiers in Behavioral Neuroscience, 2015)
Objective: Time perception is fundamental for human experience. A topic which has attracted the attention of researchers since long time is how the stimulus sensory modality (e.g., images vs. sounds) affects time judgments. However, so far, no study has directly compared the effect of two sensory modalities using emotional stimuli on time judgments. Methods: In the present two studies, healthy participants were asked to estimate the duration of a pure sound preceded by the presentation of odors vs. emotional videos as priming stimuli (implicit emotion-eliciting task). During the task, skin conductance (SC) was measured as an index of arousal. Results: Olfactory stimuli resulted in an increase in SC and in a constant time overestimation. Video stimuli resulted in an increase SC (emotional arousal), which decreased linearly overtime. Critically, video stimuli resulted in an initial time underestimation, which shifted progressively towards a time overestimation. These results suggest that video stimuli recruited both arousal-related and attention-related mechanisms, and that the role played by these mechanisms changed overtime. Conclusions: These pilot studies highlight the importance of comparing the effect of different kinds on temporal estimation tasks, and suggests that odors are well suited to investigate arousal-related temporal distortions, while videos are ideal to investigate both arousal-related and attention-related mechanisms.